Diblock/Triblock Structural Transition and Sol-Gel Transition of Peptide/PEG Diblock Copolymer Having a Terminal Terpyridine Group Induced by Complexation with Metal Ion - Hirokawa, Yoshitsugu; Yamaoka, Hitoshi; Nakamura, Yasushi; Tanimoto, Satoshi (International Journal of Polymer Science, 2010)
Terpyridine-polyethyleneglycol-block-polyleucine block copolymer (tpy-PEG-PLeu) was synthesized by a ring-opening polymerization of L-leucine N-carboxyanhydride. The copolymer complexed with Fe2+ ion and its aqueous solution showed a purple color as a result of the complexation. This complexation caused the diblock/triblock structural transition of the copolymer. The change of the aggregation behavior caused by the structural transition was observed by a dynamic light scattering apparatus. The diblock tpy-PEG-PLeu copolymer formed a micelle in the aqueous solution. On the other hand, the triblock-type copolymer, after the complexation, formed the micelle structures and huge aggregates, which is considered to be a network structure. The complexation of the diblock tpy-PEG-PLeu copolymer with Fe ion is consequently considered to be a trigger of the gelation.